Maternal Factors and Their Association with Patterns of Beverage Intake in Mexican Children and Adolescents - Lopez-Gonzalez, Desiree (Children (Basel), 2021)
Childhood and adolescence represent critical periods where beverage and food consumption behaviors are learned and developed. Mexican mothers’ presence and influence are instrumental in shaping such behaviors. The aim of this study was to estimate the prevalence and risk associations of maternal factors for unhealthy patterns of beverage intake. This study analyzed data from a population-based cross-sectional study of healthy children and adolescents from Mexico City. Data of subject’s total water intake (TWI) and its’ sources were collected using two 24-h recall surveys. Patterns of beverage intake were constructed based on the guidance system of beverage consumption in the US. Maternal factors of interest included age, body mass index (BMI), mother’s educational level (MEL), socioeconomic status (SES), and belongingness to the paid workforce (BPW). Data of 1532 subject–mother dyads informed that 47% of subjects did not meet the Institute of Medicine (IOM) recommendations for TWI, and 94.6% showed an unhealthy beverage intake pattern, mainly consisting in a lower intake of water and a higher intake of caloric beverages with some nutrients; and calorically sweetened beverages. The major sources of hydration were caloric beverages with some nutrients (i.e., whole milk, fruit water, and flavored milk). The highest risk association for an unhealthy beverage intake pattern was seen in those subjects with mothers in the cluster with lower SES, lower MEL, lower proportion of BPW, higher BMI, and younger age (OR = 9.3, 95% CI 1.2–72.8, P = 0.03). Thus, there is a remarkably high prevalence of an unhealthy pattern of beverage intake, and specific maternal factors may be implicated as enablers of such behaviors, which is also addressable for future interventions.